(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The aim of this work is to carry out a comparative analysis between oral literature and music based on the works Romancero gitano (1928) by Federico García Lorca and Howl (1958) by Allen Ginsberg. Despite their temporary and geographical distance, the study of the works shows that structures of both authors are nourished by the popular culture that surrounds them to turn it into the literary motif of their work. Finally, this analysis has shown the influence of music on these authors -whether they are of a popular nature such as romancero or flamenco in Andalusia or jazz and bebop experimental in New York-.